2021
DOI: 10.1002/pssr.202100195
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and Interfacial Effects in the Co/NixMn100−x Exchange‐Bias System due to Creation of Defects by Ar+ Sputtering

Abstract: Research on ultrathin magnetic layers and layered materials has reached an enormous impact, both scientifically and economically, with respect to applications in magnetic data storage technology, as sensors, or for future electronics utilizing the spin rather than the charge of electrons, the so-called "spintronics". [1][2][3][4] The physical size of a bit of information in magnetic data storage is already in the nanometer regime and is still shrinking, following the everincreasing demand for higher recording … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…While pure Mn does not exhibit MEED oscillations on Cu(001), it does show oscillations on Cu3$\left(\text{Cu}\right)_{3}$Au(001). [ 39 ] In the case of MnxAu1x$\left(\text{Mn}\right)_{x} \left(\text{Au}\right)_{1 - x}$ on Cu(001) with x around 0.85, we have the situation that although there are no LEED patterns, which indicates the absence of long‐range crystallographic order in the films, MEED shows intensity oscillations with monolayer periodicity. One explanation could be that on top of the first, flat monolayer of Cu–Mn–Au alloy, which grows epitaxially with the lateral lattice constant of Cu(001), there is local layer‐by‐layer growth of Mn–Au, which then, due to the large lattice mismatch to Cu(001), exhibits only short‐range lateral crystallographic order.…”
Section: Resultsmentioning
confidence: 96%
“…While pure Mn does not exhibit MEED oscillations on Cu(001), it does show oscillations on Cu3$\left(\text{Cu}\right)_{3}$Au(001). [ 39 ] In the case of MnxAu1x$\left(\text{Mn}\right)_{x} \left(\text{Au}\right)_{1 - x}$ on Cu(001) with x around 0.85, we have the situation that although there are no LEED patterns, which indicates the absence of long‐range crystallographic order in the films, MEED shows intensity oscillations with monolayer periodicity. One explanation could be that on top of the first, flat monolayer of Cu–Mn–Au alloy, which grows epitaxially with the lateral lattice constant of Cu(001), there is local layer‐by‐layer growth of Mn–Au, which then, due to the large lattice mismatch to Cu(001), exhibits only short‐range lateral crystallographic order.…”
Section: Resultsmentioning
confidence: 96%
“…We define as the blocking temperature T normalb for exchange bias the temperature below which the exchange–bias field deviates significantly from zero. [ 20 ] The blocking temperatures of the ALF and the disordered alloy samples are indicated by arrows with dotted and solid lines, respectively. The blocking temperatures of the ALF are distinctly higher than the ones of the corresponding disordered alloy films.…”
Section: Resultsmentioning
confidence: 99%
“…The two metallic elements Ni and Mn were selected in our work because they are well investigated as single‐crystalline AFM systems in the form of disordered alloys ( Ni x Mn 100 x ). [ 20–26 ] Tetragonally distorted NiMn‐disordered alloys grow in different directions on two different single crystalline substrates. On Cu(001), they grow along their a axis, while on Cu 3 Au ( 001 ) , the growth is along the c axis, yielding a uniform structural domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies on epitaxial systems suggested that bulk AF magnetic structures play a crucial role in determining EB. [5][6][7][8][9][10][11][12] For example, the domain state model [13] theorizes that bulk AF domain structures are stabilized by nonmagnetic defects when it is field cooled below the Néel temperature (T N ), and these domains carry pinned uncompensated magnetic spins and result in EB of the FM layer.…”
Section: Introductionmentioning
confidence: 99%